Major Causes & Effects of White-Collar Crimes on Corporate Sector in India: Exploring the Rise of White-Collar Crimes in the Indian Corporate Sector (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Due to the competition and mobility generated due to globalization, complexity and manyproblems have arisen in the activities of the society. Due to this dynamism, there have been changes inthe forms of crimes as well. Today's crimes are not committed due to economic poverty or due to mentaldisorder, but today's crimes are being committed by well-to-do and highly trained, prestigious and socalledwealthy people like (Nirav Modi, Vijay Mallya). Today the situation is such that every person of thesociety, political administrator, businessman and common man knows about the lack of duty of otherpeople, but finds himself helpless to do anything against them.As a result, the law is being followed, the dignity is being destroyed, there is no importance of moralvalues and every person is engaged in the competition of earning maximum profit through corruptmeans. And in this competition, we do not find women behind anywhere. Today women are also notbehind in committing such crimes, and day by day the number of crimes committed by them isincreasing a lot. We call crimes committed by women as pink collar crimes. Presently a lot of study isbeing done on pink collar crimes which shows that women commit many crimes like bootlegging,kidnapping, drug smuggling, cabaret dashing, pick pocketing, seat handling, drug addiction, shopliftingCheating, selling medicines etc. to smugglers. Many empirical studies tell us that the proportion offemale criminals is less than that of men, yet the group of criminologists believe that the crimescommitted by women are hidden by deceit or indirectly.